VARIATION IN HEAVY METAL CONCENTRATIONS OF POTATO (Solanum tuberosum L.) CULTIVARS - E. Öztürk; E. Atsan; T. Polat; K. Kara (Journal of Animal and Plant Sciences, 2011)
Heavy metals composition of foods is of immense interest because of its essential or toxic nature. This study examines concentrations of some heavy metals (Fe, Cu, Zn, Mn, Pb, Ni and Cd) from sixteen potato cultivars grown at Erzurum, Turkey. The present study revealed that the potato cultivars studied showed a considerable variation in heavy metal concentrations. The contents of heavy metals in the potato cultivars were found in the ranges: 48.87-72.64 mg kg-1 for iron, 3.07-5.43 mg kg-1 for copper, 13.80-18.89 mg kg-1 for zinc, 6.93-13.06 mg kg-1 for manganese, 0.51-0.77 mg kg-1 for lead, 2.02-3.55 mg kg-1 for nickel and 0.08-0.32 mg kg-1 for cadmium. The accumulation pattern for the metals in the potato tubers was in the order; Fe>Zn>Mn>Cu>Ni>Pb>Cd.
Keywords: Solanum tuberosum L.; potato tuber; heavy metals; concentration.